Anomalous interlayer vibrations in strongly coupled layered PdSe2*Notice: This manuscript has been authored by UT-Battelle, LLC, under contract DE-AC05-00OR22725 with the US Department of Energy (DOE). The US government retains and the publisher, by accepting the article for publication, acknowledges that the US government retains a nonexclusive, paid-up, irrevocable, worldwide license to publish or reproduce the published form of this manuscript, or allow others to do so, for US government purposes. DOE will provide public access to these results of federally sponsored research in accordance with the DOE Public Access Plan (http://energy.gov/downloads/doe-public-access-plan). (4th May 2018) - Puretzky, Alexander A; Oyedele, Akinola D; Xiao, Kai; Haglund, Amanda V; Sumpter, Bobby G; Mandrus, David; Geohegan, David B; Liang, Liangbo
Abstract: In this work, we show unusual effects of strong interlayer coupling on low-frequency (LF) Raman scattering in exfoliated PdSe2 crystals with different number of layers. Unlike many other layered materials, it is found that the measured frequencies of the breathing modes cannot be simply described by a conventional linear chain model (LCM) that treats each layer as a single rigid object. By using first-principles calculations, we show that strong deviations from layer rigidity can occur for the LF breathing vibrations of PdSe2, which accounts for the observed disagreement with the conventional LCM. The layer non-rigidity and strong interlayer coupling could also explain the unusual strong intensities of the LF breathing modes that are comparable with those of the high-frequency Raman modes. These strong intensities allowed us to use a set of the measured LF Raman lines as unique fingerprints for a precise assignment of the layer numbers. The assignment of the layer numbers was further confirmed using second harmonic generation that appeared only in the noncentrosymmetric even-layer PdSe2 crystals. This work thus demonstrates a simple and fast approach for the determination of the number of layers in 2D materials with strong interlayer coupling and non-rigid interlayer vibrations.